A qualitative assessment of emergency medicine residents' receptivity to feedback. Issue 4 (9th September 2021) - Fredette, Jenna; Michalec, Barret; Billet, Amber; Auerbach, Heather; Dixon, Jessica; Poole, Christy; Bounds, Richard
Abstract: Background: Effective feedback is the cornerstone of competency‐based education. The emergency department (ED) is a unique learning and feedback environment. Developing our understanding of emergency medicine (EM) residents' experiences around feedback will improve resident training and inform EM faculty development programs. Objective: This qualitative study explores the feedback culture and practices in EM and resident's experiences and attitudes toward feedback in this specific training environment. Methods: At a large categorical EM program, 15 residents voluntarily participated in semistructured interviews regarding feedback. These individual interviews were performed by a nonphysician investigator and transcripts underwent an inductive multistep coding process. Transcripts were analyzed to identify common factors influencing feedback and then comparisons were made between residents to explore the interconnectedness of identified factors and further categorize consistent themes. Results: Factors inherent to the ED environment make the delivery of effective feedback challenging. Residents also revealed that feedback‐seeking/‐avoidant behavior and receptivity to feedback are multifactorial. Residents actively seek feedback when they feel that they performed well but tend to avoid feedback interactions when they expect constructive feedback. Finally, residents filter feedback based on attending personality and perceived practice style as well as their own desired practice style. Conclusions: It is important for program leaders to understand their residents' experiences with feedback and engage both faculty and residents in conversations around feedback delivery and receptivity. An improved understanding of these experiences might also reveal barriers to performance assessment and guide efforts to improve the accuracy and reliability of resident evaluations.